TBX1 protein interactions and microRNA-96-5p regulation controls cell proliferation during craniofacial and dental development: implications for 22q11.2 deletion syndrome. (2nd January 2015) - Gao, Shan; Moreno, Myriam; Eliason, Steven; Cao, Huojun; Li, Xiao; Yu, Wenjie; Bidlack, Felicitas B.; Margolis, Henry C.; Baldini, Antonio; Amendt, Brad A.
Abstract: T-box transcription factor TBX1 is the major candidate gene for 22q11.2 deletion syndrome (22q11.2DS, DiGeorge syndrome/Velo-cardio-facial syndrome), whose phenotypes include craniofacial malformations such as dental defects and cleft palate. In this study, Tbx1 was conditionally deleted or over-expressed in the oral and dental epithelium to establish its role in odontogenesis and craniofacial developmental. Tbx1 lineage tracing experiments demonstrated a specific region of Tbx1-positive cells in the labial cervical loop (LaCL, stem cell niche). We found that Tbx1 conditional knockout ( Tbx1 cKO ) mice featured microdontia, which coincides with decreased stem cell proliferation in the LaCL of Tbx1 cKO mice. In contrast, Tbx1 over-expression increased dental epithelial progenitor cells in the LaCL. Furthermore, microRNA-96 ( miR-96 ) repressed Tbx1 expression and Tbx1 repressed miR-96 expression, suggesting that miR-96 and Tbx1 work in a regulatory loop to maintain the correct levels of Tbx1 . Cleft palate was observed in both conditional knockout and over-expression mice, consistent with the craniofacial/tooth defects associated with TBX1 deletion and the gene duplication that leads to 22q11.2DS. The biochemical analyses of TBX1 human mutations demonstrate functional differences in their transcriptional regulation of miR-96 and co-regulation of PITX2 activity. TBX1 interacts with PITX2 to negatively regulate PITX2 transcriptional activity and the TBX1 N-terminus is required for its repressive activity. Overall, our results indicate that Tbx1 regulates the proliferation of dental progenitor cells and craniofacial development through miR-96-5p and PITX2. Together, these data suggest a new molecular mechanism controlling pathogenesis of dental anomalies in human 22q11.2DS.